New Injury Severity Score in Fatal Blunt Thoracoabdominal Trauma in North East Delhi - Srivastava, Vivek; Kohli, Anil; Banerjee , K K (Journal of Indian Academy of Forensic Medicine, 2015)
The trauma scores provide a standardized database of autopsy findings. This may lead to  increase in the quality of trauma treatment and assessment of preventable death. Recently, researchers  have proposed a new injury severity score (NISS), which is computed as the simple sum of squares of the  three most severe AIS injuries. The present study was undertaken to focus light upon the new injury  severity score (NISS) of fatal thoracoabdominal injuries in Northeast Delhi. A total number of 93 cases  were studied during a period of one and a half years. The highlights of the study are that the largest  numbers of cases (51.6%) are in NISS 50-75 group. NISS has a mean of 46.59.There is a negative  correlation between new injury severity score (NISS) and Ps with an r-value of −0.472 (p < 0.005). An  increase in NISS leads to a decrease in period of survival.
Keywords: Thoracoabdominal Trauma; Injuries; Injury Severity Score; Fatal